2017
DOI: 10.18782/2320-7051.2769
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Correlation and Path Analysis for Quality Attributes in Sugarcane [Saccharum Spp. Hybrid]

Abstract: be made. Correlation studies provide an opportunity to study the magnitude and direction of association of yield with its components and also among various components. To accumulate optimum combination of yield contributing characters in a single genotype, it is essential to know the implication of the interrelationship of various characters along with standard partial correlation or regression (path coefficient). Considering these points, the present study was conducted to understand interrelationship among e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…This indicates improvement in these characters would simultaneously result in the improvement of cane yield and hence selection based on these characters could be advantageous. These results are in conformation with SanjayKumar and Devendra Kumar (2014) for the number of millable canes;Tena et al (2016), Pandya and. Patel (2017) for the number of millable canes and commercial cane sugar yield.…”
supporting
confidence: 74%
“…This indicates improvement in these characters would simultaneously result in the improvement of cane yield and hence selection based on these characters could be advantageous. These results are in conformation with SanjayKumar and Devendra Kumar (2014) for the number of millable canes;Tena et al (2016), Pandya and. Patel (2017) for the number of millable canes and commercial cane sugar yield.…”
supporting
confidence: 74%
“…Moreover, path coefficient analysis revealed that number of millable cane and single cane weight had the highest direct effect on cane yield than other traits Kumar, 2014 andAgrawal andKumar, 2018). Single cane weight had the highest positive direct effect on cane yield followed by millable cane number as revealed by Chaudhary andJoshi, 2005 andPandya andPatel, 2017. Path analysis revealed the highest positive direct effect of millable cane number (0.812) on cane yield followed by single cane weight (0.682) (Tena et al, 2016).…”
Section: B-cane Yield (Cy)mentioning
confidence: 97%
“…Nonsignificant but positive and weak correlation between weight of millable stalks and brix (0.05) as well as number of millable stalks and stalk height (0.285) were found by Tyagi & Lal (2007). The cane yield was positively and significantly correlated with sugar yield, single stalk weight, number of tillers and stalk length (Swamy Gowda et al, 2016;Tena et al 2016;Pandya &Patel, 2017 andAgrawal &Kumar, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A positive and highly significant correlation between cane yield and its components viz., single stalk weight, stalk length and millable cane number was reported (Panhwar et al 2003;Thippeswamy et al, 2003;Chaudhary & Joshi 2005;Kadian et al 2006;Tyagi & Lal 2007;Devendra & Sanjay 2014;Kumar & Kumar 2014;Tena et al 2016;Pandya & Patel, 2017).…”
Section: Introductionmentioning
confidence: 98%